The Effect of Sustainability Reports on FirmValue with Institutional Ownership as a Moderating Variable - Putri , Antonietha March Natasya; Bimo, Irenius Dwinanto; Sulistyaningsih, Endang (Journal of Entrepreneurship and Business, 2024)
Purpose: This research wants to enrich research that studies the effect of sustainability reporting on company performance, which is still inconsistent. In addition, this study considers the supervisory mechanism factor in the form of institutional ownership to determine whether the effect of sustainability reporting on company performance is different in companies with high institutional ownership and companies with low institutional ownership. Method: The study utilized purposive sampling to select companies listed on the Indonesia Stock Exchange (IDX) that consistently published both sustainability and financial reports from 2017 to 2020, resulting in a sample of 39 companies. For hypothesis testing, the research employed the STATA 17 software, followed by methods such as descriptive analysis, panel data regression analysis, determination of coefficients, and tests for both simultaneous and partial significance. Result: Sustainability reporting positively influences firm value. This study found that institutional ownership moderates the effect of sustainability reporting on firm value. Future research should focus on examining companies within similar sectors to yield more reliable results concerning how sustainability reports affect firm value, considering the specific characteristics of companies across different industry.